PENERAPAN METODE SAW UNTUK SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK PADA SMK TRIMULYA DI SEMARANG - Rutna Anggaraeni; Oktaga, Andreas Tigor; Prihati; Martius Apun Heses; Kristiawan Nurdianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2025)
The purpose of this research is to reveal the advantages of the Simple Additive Weighting (SAW) method in measuring lecturer performance to produce the best lecturer assessment. This research uses Purposive Sampling technique in determining student participants in the SMK TRIMULYA to select five teachers who have provided learning to all participants. The criteria used are discipline, teaching, motivation and innovation. The results of this study obtained the calculation results, namely teacher 1 (G1) with a total of 0,62, teacher 2 (G2) with a total of 0,60, teacher 3 (G3) with a total of 0,80, teacher 4 (G4) with a total of 1,00, and teacher 5 (G5) with a total of 0,72. So it can be concluded that the decision support system using the SAW method shows that the highest score is teacher 4 (G4). The SAW method is expected to help SMK TRIMULYA to determine the best teachers in the following periods.